1996
DOI: 10.1073/pnas.93.24.14025
|View full text |Cite
|
Sign up to set email alerts
|

Frequent clones of p53-mutated keratinocytes in normal human skin

Abstract: The multiple genetic hit model of cancer predicts that normal individuals should have stable populations of cancer-prone, but noncancerous, mutant cells awaiting further genetic hits. We report that whole-mount preparations of human skin contain clonal patches of p53-mutated keratinocytes, arising from the dermal-epidermal junction and from hair follicles. These clones, 60-3000 cells in size, are present at frequencies exceeding 40 cells per cm 2 and together involve as much as 4% of the epidermis. In sun-expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
450
3
18

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 625 publications
(506 citation statements)
references
References 29 publications
30
450
3
18
Order By: Relevance
“…BCCs are unusual in that they are apparently genetically stable and no precursor lesion has been identified. In humans, p53 mutations occur very frequently in BCCs as well as in patches of morphologically normal skin, especially in UV-exposed areas (32,45). On the basis of these observations, it has been suggested that p53 mutations are an early and required event in BCC development.…”
Section: Discussionmentioning
confidence: 99%
“…BCCs are unusual in that they are apparently genetically stable and no precursor lesion has been identified. In humans, p53 mutations occur very frequently in BCCs as well as in patches of morphologically normal skin, especially in UV-exposed areas (32,45). On the basis of these observations, it has been suggested that p53 mutations are an early and required event in BCC development.…”
Section: Discussionmentioning
confidence: 99%
“…UVB induces a characteristic type of mutation (a C-to-T transition at a dipyrimidine site) (3). These signature mutations are commonly found in the p53 gene in sun-exposed (yet apparently normal) skin, sun-damaged epidermis, premalignant lesions known as actinic keratoses, and in squamous carcinomas, consistent with p53 mutation being an early event in the clonal evolution of UVB-induced SCC (4)(5)(6)(7). Keratinocytes lacking functional p53 have a greatly increased risk of malignant transformation from UVB irradiation, suggesting that the size of the p53 mutant population in epidermis will determine cancer risk (8).…”
mentioning
confidence: 88%
“…The established role of p53 in the genesis of SCC suggested that deficiency of this tumor suppressor could promote the KLF4-induced phenotype (Boyle et al, 1993;Kemp et al, 1993;Ziegler et al, 1994;Jonason et al, 1996;Brash and Ponten, 1998;Jonkers et al, 2001). We identified settings in which p53 deficiency was important or essential for KLF4-induced dysplasia (Figures 5 and 6).…”
Section: P53 Deficiency Promotes Klf4-induced Dysplasiamentioning
confidence: 99%